Biostability of the Proanthocyanidins-Dentin Complex and Adhesion Studies. (April 2017) - Leme-Kraus, A.A.; Aydin, B.; Vidal, C.M.P.; Phansalkar, R.M; Nam, J.W.; McAlpine, J.; Pauli, G.F.; Chen, S.; Bedran-Russo, A.K.
Oligomeric proanthocyanidins (OPACs) are potent and renewable natural bioactives possible to be refined into chemically standardized mixtures for biological applications. Herein, we found that multiscale interactions of OPACs with the dentin matrix create tight biointerfaces with hydrophobic methacrylate adhesives on wet surfaces. An enriched mixture of OPACs, with a known phytochemical profile, was produced from grape seed crude extract ( Vitis vinifera ; enriched grape seed extract [e-GSE]) and applied to dentin matrices to determine changes to the mechanical properties and biodegradability of the dentin matrix and favorable resin adhesion mechanisms. Methods included a 3-point flexural test, quantification of hydroxyproline (collagen solubilization), static and dynamic nanomechanical analyses, resin-dentin microtensile bond strength, and micropermeability at the adhesive interface. The e-GSE-modified dentin matrix exhibited remarkably low collagen solubilization and sustained the bulk elastic properties over 12 mo. Tan δ findings reveal a more elastic-like behavior of the e-GSE-modified dentin matrix, which was not affected by H-bond destabilization by urea. Dentin-methacrylate biointerfaces with robust and stable adhesion were created on e-GSE-primed dentin surfaces, leading to a dramatic decrease of the interfacial permeability. Standardized OPAC mixtures provide a new mechanism of adhesion to type I collagen–rich tissues that does not rely on hydrophilic monomers. The bioadhesion mechanism involves physicochemical modifications to the dentin matrix, reduced tissue biodegradation, and bridging to methacrylate resins.